Clinical and functional assessment of SARS-CoV-2 sequelae among young marines - a panel studyResearch in context - Chad K. Porter; Charmagne G. Beckett; Elizabeth Cooper; Lindsey White; David Wallace; Silvia Jakubski; David Boulifard; Megan Schilling; Peifang Sun; Jan Marayag; Amethyst Marrone; Edgar O. Nunez-Hernandez; et al. (Elsevier, 2024)
Summary: Background: Long-term SARS-CoV-2 adverse health outcomes are of significant concern, especially among young adults with the potential for the greatest long-term morbidity. We sought to assess and characterize these outcomes in a cohort of Marines. Methods: We used a cohort of US Marines from a previous longitudinal, prospective observational study of acute SARS-CoV-2, most of whom were enrolled prior to infection. A panel study was established to assess for post-acute sequelae of COVID-19 (PASC), defined as symptoms at least 4 weeks after symptom onset or diagnosis. Symptoms were assessed through questionnaires and validated quality of health metrics. Periodic US Marine Corps fitness testing metrics provided an additional standardized functional assessment and were compared to a pre-pandemic cohort. Findings: Globally dispersed Marine participants (n = 899) seen an average of 330 days following initial enrollment were predominately male (n = 825, 91.7%), White (n = 613, 71.6%) or Black (n = 149, 17.4%) with a median age of 18 years (interquartile range: 18-19). Among 798 SARS-CoV-2 infected participants, 197 (24.7%) developed PASC. The most prevalent symptoms were loss of taste and/or smell (n = 82; 41.6%), shortness of breath (n = 74; 37.6%), and cough (n = 45; 22.8%). Those with PASC had higher rates and severity of somatic (p < 0.0001), general depressive (p < 0.0001), and anxiety (p = 0.005) symptoms. Compared to a historic cohort of Marines, participants with PASC scored worse on their physical fitness assessments due to slower run times (p = 0.002). Those with PASC continued to have decreased physical performance one year after completing initial training. Interpretation: In this population of healthy young adult US Marines with mostly either asymptomatic or mild acute COVID-19, one fourth reported physical, cognitive, or psychiatric long-term sequelae of infection. The Marines affected with PASC showed evidence of long-term decrease in functional performance suggesting that SARS-CoV-2 infection may negatively affect health for a significant proportion of young adults. Funding: Defense Health Agency and Defense Advanced Research Projects Agency.